2013
DOI: 10.1007/s00198-013-2268-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum extracellular secreted antagonists of the canonical Wnt/β-catenin signaling pathway in patients with Cushing’s syndrome

Abstract: Of all the tested proteins (sclerostin, Dkk1, SFRP1), only sclerostin showed a significant difference when contrasting CS with healthy subjects. Hypercortisolism might prevent the down-regulation of sclerostin. Targeting sclerostin seems to be a promising therapeutic approach to treating osteoporosis in patients with CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
0
21
0
5
Order By: Relevance
“…Yet another study described that sclerostin levels were decreased in patients with endogenous hypercortisolism, and increased after correction [21]. In contrast, Belaya et al reported recently high sclerostin values in patients with Cushing's syndrome [22]. Although it is tempting to speculate that the high steroid dosage immediately after transplantation might have contributed to the rapid decrease of the sclerostin levels, this requires further studies.…”
Section: Discussionmentioning
confidence: 89%
“…Yet another study described that sclerostin levels were decreased in patients with endogenous hypercortisolism, and increased after correction [21]. In contrast, Belaya et al reported recently high sclerostin values in patients with Cushing's syndrome [22]. Although it is tempting to speculate that the high steroid dosage immediately after transplantation might have contributed to the rapid decrease of the sclerostin levels, this requires further studies.…”
Section: Discussionmentioning
confidence: 89%
“…34–38 Yet, the evidence for a substantial link in human patients has been discordant with decreased serum sclerostin at one week in GC patients, 39 and increased serum sclerostin at later time points. 40 Similar disparities are seen with sclerostin and disease states: increased levels are reported in Cushing’s syndrome patients, 41 whereas cases of chronic hypercortisolism presented with decreased sclerostin. 42 Sclerostin activity as a means for heavy metals to facilitate osteoporotic bone loss was first established in animal systems 19,43–45 and their association was recently revealed in osteoporotic patients.…”
Section: Introductionmentioning
confidence: 79%
“…However, its significance in the development of glucocorticoid-induced bone loss is not completely clear. Recently, higher levels of sclerostin, an extra-cellular antagonist of the Wingless/β-catenin (Wnt) signaling pathway, were noted in patients with Cushing’s syndrome compared to healthy individuals (22). However contradictory results were found in another study (266).…”
Section: Clinical Features Of Cushing’s Syndromementioning
confidence: 99%